Majstorkning - Åkesson, Erik (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The corn plant came to Europe with Christopher Columbus in the 14th century and have ever since bin cropped here, but corn haven't bin very common in Scandinavia until recently. The mainly use for this crop silage but even corn for grain is cropped in Europe. Corn for grain is a common part of feed in beef and chicken farming. In Sweden corn for grain is pretty rare but almost 1000 hectares are used for this crop, Lantmännen Sverige is the biggest buyer of corn at the moment. The summer in Sweden is short and whet, therefore corn is harvested with a high moister content. It is hard to harvest corn under 40 % moisture content a whet year with a cold summer but a good year when the summer is warm and the autumn dry you can harvest corn with less than 30 % moisture. My goal with this examination work is to give Swedish farmers a good idea of how to dry corn and what it costs to do it. Now days when the price of energy are very high, the drying costs are rising and getting the biggest issue of the economy in cropping corn for grain therefore I find it important to find new ways to dry corn as cheep as possible. To find out how much fuel it takes to dry corn I did a trial in the harvest 2006 on the dryer on my parent's farm. I also did a couple of interviews, studied trials and looked at advising for corn growers in the USA. Because of the high levels of moister content you get in corn when it gets to harvest, its best to dry it in to stages. Under Swedish circumstances it is hard to move water from the centre of the big corn kernels, thru the hard starch layer in the surface and out in the air. It is important to no harvest more corn than you have capacity to dry, whet corn rapidly gets warm and starts to rotten if you not start to dry it immediately. On an average year in Swedish conditions you need about 45 litres of diesel fuel to make a ton of dry corn. The conclusion of my examination work is as following: Corn should be dried with high temperatures on the drying air to make it an efficient drying process. You should also use a transportation equipment in your system that are treating the grain carefully, the corn kernels are very easy damage. Problems that you can find when it gets to corn drying is hot spots in stacks off whet corn not being dried. The best way to avoid this problem is to not harvest more con per day than your dryer have capacity to take care of. Under Swedish circumstances it is necessary to dry corn to times to get all the water you need out of the corn kernel. Finally, the costs for the energy it requires to dry corn an average year is about 250 Swedish crowns per metric ton of dried corn.